Knowledge and Attitude on Pain Management among Final Year Nursing and Midwifery Students of Khesar Gyalpo University of Medical Sciences of Bhutan - ., Kuenzang; Pokhrel, Hari Prasad; Sherpa, Passang Lhamo (International Journal of Innovative Research in Medical Science, 2018)
Pain management is the most important component of nursing care process and it is crucial for nurses to have a good level of knowledge on pain management. A cross-sectional study was conducted among 44 final year General Nursing and Midwifery students at the Faculty of Nursing and Public Health, Khesar Gyalpo University of Medical Sciences of Bhutan in May 2016. Independent samples T- test was used to assess the association. The mean (SD) age of the respondents was 22.66 years (1.26). Over two-thirds (81.8%) of the participants had a poor level of knowledge and a majority (90.9%) of them had never been posted to a pain clinic. Over a half of them (56.8%) had negative attitude towards pain management. Independent samples t-test detected a significant difference in the mean knowledge scores between students who regularly used pain assessment scales and those who did not use the scales respectively. The study recommends to include pain management as a standalone module to better equip the nurses with knowledge on pain management. Mandatory posting of the students in pain clinic will provide the students with an opportunity to practice the skills.